2021
DOI: 10.24099/vet.arhiv.1087
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the lipid profile of neutered cats’ blood in cases of obesity and diabetes

Abstract: The aim of the present study was to examine the lipid profile, lipid fractions and the lipid peroxidation state in the blood of neutered cats with obesity and diabetes. Three groups of neutered cats (males and females) were formed for the study. We compared cats with obesity (7-9 points on a 9-point BCS scale), with obesity complicated by diabetes, and clinically healthy animals with normal body condition scores (4-5 BCS points). Lipidogram parameters, fractions of high-density lipoprotein (HDL), low-density l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…Serum TAG concentrations were also similar to those previously reported in healthy adult cats ( 55 , 56 ). The present results align with previous reports of similarly higher circulating TAG, VLDL and lower HDL-C in obese cats, as compared to a lean control group ( 57 60 ). However, said authors also reported greater circulating NEFA, CHOL, and LDL-C concentrations in obese cats, which was not observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serum TAG concentrations were also similar to those previously reported in healthy adult cats ( 55 , 56 ). The present results align with previous reports of similarly higher circulating TAG, VLDL and lower HDL-C in obese cats, as compared to a lean control group ( 57 60 ). However, said authors also reported greater circulating NEFA, CHOL, and LDL-C concentrations in obese cats, which was not observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…However, said authors also reported greater circulating NEFA, CHOL, and LDL-C concentrations in obese cats, which was not observed in the present study. As the mean age of the cats in the present study was lower than the mean age reported in these previous studies ( 57 , 60 ), it is unclear if age may have also had an impact. To our knowledge, the effect of age on serum lipid, biochemistry and/or metabolomic profiles in overweight or obese cats has not specifically been investigated.…”
Section: Discussioncontrasting
confidence: 84%
“…At an adequate level of incorporation, EPA and DHA infl uence the membrane fl uidity as well as membrane protein-mediated reactions, generation of lipid-mediators, cell signaling, and gene expression in different cells [32]. Data on cats, together with the results of lipoprotein analysis, indicate possible disturbances in the hepatic transformation of LDL and VLDL, and a high risk of atherogenic events [33]. Dogs have the capacity to metabolize n-3 fatty acids and the effects of omega-3 fatty acids on the skin and coat, infl ammatory responses, and neurologic development in puppies are quite visible [34].…”
Section: Discussionmentioning
confidence: 99%